Fuzzy Amicable sets of an Almost Distributive Fuzzy Lattice - Berhanu Assaye Alaba; Yohannes Gedamu Wondifraw; Bekalu Tarekegn Bitew ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2017)
In this paper, we introduce the concept of Fuzzy Amicable sets, we prove some properties of Fuzzy Amicable set, too. We also prove that two Fuzzy compatible elements of an Almost distributive Fuzzy Lattice (ADFL) are equal if and only if their corresponding unique Fuzzy amicable elements are equal. We define the homomorphism of two Almost Distributive Fuzzy lattices (ADFL) and finally we observe that any two Fuzzy amicable set in an Almost Distributive Fuzzy Lattice (ADFL) are isomorphic.